Schisantherin A inhibits cell proliferation by regulating glucose metabolism pathway in hepatocellular carcinoma - Fan Feng; Lianhong Pan; Jiaqin Wu; Mingying Liu; Long He; Li Yang; Wei Zhou (Frontiers Media S.A., 2022)
Schisantherin A (STA) is a traditional Chinese medicine extracted from the plant Schisandra chinensis, which has a wide range of anti-inflammatory, antioxidant, and other pharmacological effects. This study investigates the anti-hepatocellular carcinoma effects of STA and the underlying mechanisms. STA significantly inhibits the proliferation and migration of Hep3B and HCCLM3 cells in vitro in a concentration-dependent manner. RNA-sequencing showed that 77 genes are upregulated and 136 genes are downregulated in STA-treated cells compared with untreated cells. KEGG pathway analysis showed significant enrichment in galactose metabolism as well as in fructose and mannose metabolism. Further gas chromatography-mass spectrometric analysis (GC-MS) confirmed this, indicating that STA significantly inhibits the glucose metabolism pathway of Hep3B cells. Tumor xenograft in nude mice showed that STA has a significant inhibitory effect on tumor growth in vivo. In conclusion, our results indicate that STA can inhibit cell proliferation by regulating glucose metabolism, with subsequent anti-tumor effects, and has the potential to be a candidate drug for the treatment of liver cancer.